2001
DOI: 10.1002/path.917
|View full text |Cite
|
Sign up to set email alerts
|

hTERT expression in sporadic renal cell carcinomas

Abstract: Human telomerase is a specialized reverse transcriptase that catalyses telomeric repeat addition at the ends of chromosomes. Activation of this enzyme is one of the key steps in cell immortalization and carcinogenesis, and one of its components, hTERT, is considered as the rate-limiting factor. While telomerase activity was found to be prognostically relevant in various cancers, results obtained from renal cell carcinomas (RCC) failed to show any correlation with the usual prognostic factors. The aim of the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…Earlier clinical investigations have shown that telomerase activity is only detectable in RCC tumors but not in adjacent normal renal tissues, however, both normal and malignant tissues may express hTERT mRNA, a rate-limiting component for telomerase activity (11,15,17). To determine whether this was also the case for our cohort of patients, we employed the specific hTERT primers 1,784/1,928, used in above studies (15,17), to PCR amplify hTERT transcripts in 33 RCC tumors and their corresponding normal tissues.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier clinical investigations have shown that telomerase activity is only detectable in RCC tumors but not in adjacent normal renal tissues, however, both normal and malignant tissues may express hTERT mRNA, a rate-limiting component for telomerase activity (11,15,17). To determine whether this was also the case for our cohort of patients, we employed the specific hTERT primers 1,784/1,928, used in above studies (15,17), to PCR amplify hTERT transcripts in 33 RCC tumors and their corresponding normal tissues.…”
Section: Resultsmentioning
confidence: 99%
“…Concordantly, a significant association between full length hTERT RNA, telomerase activity and cMyc induction in RCC was recently demonstrated, further strengthening the connection between cMyc and hTERT. 23 In contrast, a smaller series of RCC showed no correlation between cMyc and hTERT mRNA levels 22 but indicated that cRCC had lower hTERT and telomerase activity levels than nonccRCC. The latter finding is obviously in contrast to our analysis, which was based on a larger series of tumors.…”
Section: Discussionmentioning
confidence: 98%
“…21 However, inconsistent observations have been noted regarding a connection between cMyc and hTERT gene expression in RCC. 22,23 PKB/Akt can also affect telomerase expression through post-transcriptional phosphorylation of the hTERT protein as indicated in studies on myeloma and ovarian cancer cells. 24,25 Thus, the PI-3-kinase-PKB/Akt pathway can interact with hTERT and telomerase expression at both the transcriptional and posttranscriptional level and since DJ-1 might be a potentially important regulator of this pathway the present study was undertaken to further investigate this issue in RCC.…”
mentioning
confidence: 99%
“…A requirement of 70 -80% of cancer cells seems reasonable in order to compare telomerase levels to external standards provided by cell lines (Marchetti et al, 2002). Furthermore, the exactitude of any measurement of telomerase activity is challenged by intratumoral heterogeneity of hTERT expression (Kumaki et al, 2001;Paradis et al, 2001). We and others have experienced successful hTERT in situ hybridisation approaches, which evaluate the level of transcription of hTERT (Kolquist et al, 1998;Soria et al, 2001;Wang et al, 2002).…”
Section: Discussionmentioning
confidence: 99%